Topics in Applied Physics
DOI: 10.1007/3-540-39947-x_10
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spectroscopy Studies of Carbon Nanotubes

Abstract: Abstract. Electron spectroscopies play an essential role in the experimental characterization of the electronic structure of solids. After a short description of the techniques used, the paper reviews some of the most important results obtained on purified single-and multi-wall carbon nanotubes, and intercalated nanotubes as well. An analysis of the occupied and unoccupied electron states, and the plasmon structure of the nanotubes is provided. How this information can be used to characterize the samples is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The surface work function of the sample obtained from the SECO is 4.24 ± 0.10 eV, which is slightly lower than the work function (4.5–4.6 eV) of pristine graphene and graphite. , Figure b shows the valence band structure of the nanotubes. Two main peaks at ∼3 eV (π- band) and ∼8 eV (σ-band) below E f can be identified, which are the typical features found in the s-SWCNT spectrum …”
Section: Results and Discussionmentioning
confidence: 79%
“…The surface work function of the sample obtained from the SECO is 4.24 ± 0.10 eV, which is slightly lower than the work function (4.5–4.6 eV) of pristine graphene and graphite. , Figure b shows the valence band structure of the nanotubes. Two main peaks at ∼3 eV (π- band) and ∼8 eV (σ-band) below E f can be identified, which are the typical features found in the s-SWCNT spectrum …”
Section: Results and Discussionmentioning
confidence: 79%
“…This is likely to be caused by higher ordering in graphitic stacking and diminishing defect density. 35 …”
Section: F Discussionmentioning
confidence: 97%
“…The second dispersive feature, a high-energy peak located in the range of 21-25 eV, originates from s + p-plasmon excitation. The lower energy of the s + p-plasmon in SWCNTs -as compared to graphite -results from the anisotropy of the graphene layer in the nanotubes [242]. More recently, EELS studies on individual SWCNTs have demonstrated that both the p-and the s + p-plasmon have two components, namely a bulk and a surface mode, with the former appearing at slightly higher energies [198,199].…”
Section: Electron Energy Loss Spectroscopymentioning
confidence: 98%
“…While in the initial UPS experiments, it has been impossible to observe a fine structure reflecting the vHs in the density of occupied states, even when the spectra were recorded with the highest energy solution [242], this task has recently been reached with more homogeneous SWCNT samples [250]. This achievement has significantly contributed to an understanding of many-electron effects in SWCNTs.…”
Section: Photoelectron Spectroscopymentioning
confidence: 99%